Esensi Wahyu Dan Ilmu Pengetahuan - Rosita Baiti; Abdur Razzaq (Wardah, 2017)
This study discusses the related of revelation with science. Reviewing revelation does not mean ignoring the study in the perspective of science, because in the revelation itself is found so many verses that encourage human beings to conduct thinking activities in reviewing everything especially the universe for the creation of a civilized life. Science has indeed contributed greatly to the welfare of live and life, but it is realized that the results of science especially concerning truths that have a high value can not be obtained. Therefore, the information of revelation becomes important and needed by humans in addition to cover the weaknesses of science, but also as a guide to life for the happiness of the world and the hereafter.